Engineering optimization : methods and applications Ed 2 - Ravindran A and others; Ragsdell K M; Reklaitis G V (New Delhi Wiley, 2018)
In the most general terms, optimization theory is a body of mathematical results and numerical methods for finding and identifying the best candidate from a collection of alternatives without having to explicitly enumerate and evaluate all possible alternatives. The process of optimization lies at the root of engineering, since the classical function of the engineer is to design new, better, more efficient and less expensive systems as well as to devise plans and procedures for the improved operation of existing systems. Most optimization routines are lengthy and therefore are efficiently applied through the use of the computer, but an understanding of the processes is needed to identify needs and interpret results. This book supplies the student and practicing engineer with the tools to understand and use optimization theory.
Keywords: Linearization; Engineering Case Studies; Quadratic Approximation; Linear Algebra